Pharmaceutical Education and Studying: Development of Pharmaceutical Education Programs and Studying of Specialists in the Field - Iryna Borysiuk,; Nataliia Veresniuk,; Mykola Opanasiuk,; Vadym Didychuk, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Pharmaceutical education plays an important role for the education and health care system of the country and the world, because errors related to the action of medicines can sometimes be fatal. Pharmaceutical education programs are regulated at the legislative level and require constant improvement to solve problems of modern society. Our research is aimed at determining the main principles of modern pharmacological education in Ukraine and Europe. According to the literature, a paradigm shift in the training of pharmacists from a production direction to a patient-oriented model has been determined. In accordance with this paradigm, the competencies and skills that must be mastered while studying in pharmaceutical schools have been formed such as: flexibility, communication, analytical and critical thinking, ethics, the ability to learn quickly, etc. In order to achieve competitive competencies, educational programs should be student-oriented, teachers should be creative and highly qualified, and educational institutions should be provided with a sufficient level of material and technical support.